RUMAH SAKIT JIWA DI KOTA SAMPIT - Bilhairini, Isra; Sutrisno, Herwin; Susi, Theresia (JURNAL PERSPEKTIF ARSITEKTUR, 2023)
Mental health is one of the most important aspects in realizing overall physical, spiritual and physical health. Patients with mental disorders need appropriate treatment and rehabilitation facilities and are able to provide a place for the healing process, with the existence of a mental hospital is expected to be able to help cure mental disorders both physically, socially and spiritually as a place for ODGJ and drug addicts to be ready to return healthily and productively in the community. Based on Basic Health Research (Riskesdas) conducted in 2018 in Central Kalimantan, East Kotawaringin Regency (Kotim) is the region that has the highest weighted value index compared to other regions in Central Kalimantan in mental disorders. In line with this, Kotim Regency urges to have a mental hospital to accommodate people with mental disorders and drug addicts. The design of this mental hospital emphasizes safety and comfort factors in its design. The safety related to the design standards of mental hospitals and patient comfort in them related to the five sensory elements, namely visual, texture, sound and smell, namely by using a therapeutic architectural approach, because according to Morganthaler (2015) the architecture itself does not claim to have the ability to heal people, but rather "architectural manipulation of structures and spaces that can allow environmental factors such as sound, Color, sight, smell and light contribute to a therapeutic environment that makes them stand out for healing purposes." This design method uses descriptive qualitative methods including data collection by means of surveys, interviews, and literature reviews on mental hospitals and therapeutic architecture. The result of the design is to produce the design of a Mental Hospital in Sampit City that can accommodate security and psychological comfort through the five senses with a Therapeutic Architecture approach.